INTRAMOLECULAR CYCLIZATION OF 3-(2-CARBOXYPHENYL)- AND 3-(2-CARBOXYBENZYL) ISOCOUMARINE: UDC 547.814.5 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Intramolecular cyclization of 3-(2-carboxyphenyl)- and 3-(2-carboxybenzyl)isocoumarin under the action of strong mineral acids was investigated. The behavior of resulting condensed systems in alkaline medium was studied.
Keywords: intramolecular acylation, 5,11-dihydro-indeno[1,2-c]isochromen-5,11-dione, 5H-dibenzo[c, g]chromen-5-one.